Periodontal health status of heavy and light smokers and its correlation with salivary superoxide dismutase enzyme (A comparative study) - Banaz J Ali; Leka'a M Ibrahim; Ali Y Majid (College of Dentistry/ University of Baghdad, 2014)
Background: Periodontal disease is a chronic bacterial infection that affects the gingiva and bone supporting the teeth. Smoking, which is an important risk factor for periodontitis, induce oxidative stress in the body and cause an imbalance between reactive oxygen species (ROS) and antioxidants, such as superoxide dismutase (SOD). This study aimed to evaluate the influence of smoking on periodontal health status by estimating the levels of salivary SOD level in non-smokers (controls) and light and heavy smokers and to test the correlation between the SOD enzyme level and the clinical periodontal parameters in each group. Materials and Methods: The study sample consisted of 75 male, with age ranged from 35 to 50 years. Clinically, the periodontal parameters used in this study were Plaque index (PLI). Gingival index (GI), probing pocket depth (PPD), Bleeding on probing (BOP) and clinical attachment level (CAL), unstimulated saliva sample were collected from all subjects and the levels of superoxide dismutase enzyme was analyzed for each group , and correlate the mean of salivary enzyme levels with the clinical periodontal parameters. Results: Highly significant differences in PLI between (non smokers/heavy smokers) and (light smokers/heavy smokers).On the other hand no significant difference in gingival index between groups. There were a high association between severity of smoking & probing pocket depth and there is association between severity of smoking and clinical attachment loss. There were a significant difference in the level of salivary superoxide dismutase enzyme between the (non smokers/light smokers) groups & between (heavy smokers/light smokers) &there were highly significant differences between (non smokers/heavy smokers) groups. There is no correlation between the activities of the salivary superoxide dismutase enzyme and the clinical periodontal parameters except in SOD with (BOP score 0 and PPD score 1&score 3) in heavy smokers group. Conclusions: Superoxide dismutase enzyme can be used as biomarker for estimating the level of oxidative stress on smoking habits.